Arola, Raimon. El Tarot de Mantegna. Vitoria-Gasteiz: Sans Soleil Ediciones, 2021 [ISBN: 978-84-121578-6-4]Arola, Raimon. El Tarot de Mantegna. Vitoria-Gasteiz: Sans Soleil Ediciones, 2021 [ISBN: 978-84-121578-6-4] - Boj Pérez, Laura (Eikón / Imago, 2023)
Book review of Arola, Raimon. El Tarot de Mantegna. Vitoria-Gasteiz: Sans Soleil Ediciones, 2021 [ISBN: 978-84-121578-6-4]